Health risk assessment of heavy metals in imported frozen fish sold in Damaturu and Maiduguri fish markets, Nigeria - Jajere, S. M.; Jidda, D.; Goni, M.D.; Sadiq, M.A.; Adamu, S. G.; Mohammed, S.; Saidu, A. S.; Malah, M.; Musa, H. I.; Tijjani, A. O. (Faculty of Veterinary Medicine, University of Maiduguri, 2023)
Heavy metals bioaccumulation in fish constitute an issue of public health concerns. This study aimed to evaluate the levels of Cadmium (Cd) and Lead (Pb) in the head and muscle tissues of imported frozen fish as well as health risk to man. A total of 30 frozen fish were sampled from different fish markets in Damaturu and Maiduguri in Yobe and Borno States, Nigeria respectively. Heavy metal concentrations were determined by atomic absorption spectrophotometer. The highest mean concentration levels (0.60 ± 0.32 mg/kg and 0.06 ± 0.10 mg/kg) of Pb and Cd were found in the head and the lowest (0.09 ± 0.02 and 0.01 ± 0.00) in the muscle tissues respectively. The mean concentration levels of Pb (0.60 ± 0.32 mg/kg) and Cd (0.06 ± 0.10 mg/kg) in fish markets A and D exceed the maximum allowable limits of 0.50 mg/kg and 0.05 mg/kg respectively. Fish markets had statistically significant (p < 0.05) effect on the concentration levels of Pb among the sampled fish. The assessment of potential health risk; estimated daily intake, the target cancer rate, target hazard quotient and hazard index values obtained were below the threshold, indicating consumption of head and muscle of imported frozen fish sold in the study areas is safe and hazardless. However, because of their non-degradable nature and tendency to accumulate in tissues and organs, we recommended that heavy metals contamination in imported frozen fish should be monitored regularly, and packages should contain concentration labels before releasing it into the market value chain.